Assessing the Effects of Dermatological Disorders: A Comparative Study of Quality of Life and Psychological Symptoms in Outpatient and Hospitalized Patients - Faryal Ghulam Hussain Memon, Sajida Bibi, Fatima Sajid, Sarmad Nasir, Zill-E-Huma Tariq, Afnan Bin Haq, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Dermatological disorders encompass a diverse array of conditions affecting the skin, hair, and nails, exerting a profound impact on individuals' quality of life (QOL) and psychological well- being. This study aims to compare QOL and psychological symptoms among dermatology patients across outpatient and hospitalized settings, as well as healthy controls, to elucidate potential variations in outcomes across care settings. Methodology: A total of n=701 outpatient dermatology patients, hospitalized dermatological patients n=349, and outpatients n=352 healthy controls were recruited for the study. Participants completed measures assessing depression, anxiety, and QOL. Results: Hospitalized dermatological patients exhibit significantly lower QOL and higher psychological distress compared to outpatients and healthy controls. Specific dermatological diagnoses, such as psoriasis and atopic dermatitis, are associated with greater psychological symptomatology and reduced QOL. Disease-related impairment of QOL emerges as a robust predictor of psychological symptoms, highlighting the interconnectedness of physical and psychological well-being in dermatology patients. Conclusion: Our findings underscore the importance of integrated care models that address both the dermatological and psychological aspects of patient care. By elucidating the factors contributing to patients' psychosocial burden and treatment outcomes, our study informs tailored interventions aimed at optimizing patient- centered care and improving overall QOL for individuals grappling with dermatological disorders. Keywords: Dermatological disorders, Quality of life, Psychological distress, Outpatient Hospitalized Healthy controls, integrated care